Acculturation, Physical Activity, and Metabolic Syndrome in Asian American Adults. (November 2022) - Sheng, Jingxi; Abshire, Demetrius A.; Heiney, Sue P.; Wirth, Michael D.
Introduction: Asian Americans (AsAms) have a high prevalence of metabolic syndrome (MetS) and are one of the least physically active racial groups in America. The purpose of this study was to examine the relationship between MetS and moderate-to-vigorous physical activity (MVPA) among AsAm adults and whether acculturation modifies this relationship. Method: Data were from 2, 259 AsAms participating in the 2011–2016 National Health and Nutrition Examination Survey. Physical activity (PA) was self-reported as minutes of weekly MVPA. Acculturation included nativity, length of residency in America, and language preference. The International Diabetes Federation criteria was used to determine the presence of MetS. Results: About 64.4% of AsAms did not meet the PA recommendation (MVPA ≥150 min/week). The prevalence of MetS was 39.2%. The odds of having MetS were greater among AsAms who did not meet MVPA recommendations compared with those who did meet MVPA recommendations (odds ratio [OR] = 1.5, 95% confidence interval [CI] = [1.11, 2.07]). When stratified by acculturation, this association remained statistically significant in the groups who immigrated to America more than 15 years ago and who spoke English only. Conclusion: MVPA reduces MetS risk in AsAm adults, especially among more acculturated AsAms. Culturally adapted programs are warranted to promote PA and adequate knowledge of disease prevention in this population.